Proceedings of the International school of Physics “Enrico fermi” Course CLXXIX - Ferroni, F (IOS Press, 2014)
In the past decade, laser-plasma acceleration has shown an impressive progress, with outstanding achievements from both experimental and theoretical viewpoints. Exploiting closely the development of ultraintense, ultrashort pulse lasers, laser-plasma acceleration has rapidly developed, showing accelerating gradients of tens of GeV/m and making the vision of miniature accelerators more realistic than ever. Indeed, the growing interest of the wider scientific community is now leading to joint programmes that see two communities, the laser-plasma and the high-energy physics community working side by side for a common objective